Efficient learning strategies: Student attraction to entrepreneurship lessons using technology - Azmy Ramelan Kurniawan; S. Sistiyani; Zalfa Feyza Qolbi (Universitas Pendidikan Indonesia, 2024)
Education is an essential foundation in shaping the future of individuals and the progress of a country. However, the education system often faces challenges in effectively meeting learners' needs, mainly due to monotonous learning methods and a mismatch with individual learning styles. In addition, increasing learning productivity is a primary goal in education. ICT integration is the key to improving the quality of learning. Thus, this research combines learning styles, ICT integration, and strategies to improve learning productivity to create effective and relevant education. This research uses a descriptive approach with data collection techniques in the form of questionnaires. The collected data were analyzed to understand various aspects related to learning styles, ICT integration, and learning productivity strategies. This research shows that learning strategies are crucial in educational services to increase understanding and effective student learning applications. In addition, using technology in entrepreneurship learning can increase students' interest in learning and experience.